Excavations carried out by H.M. Office of Works in the Bronze Age Levels at Jarlshof in 1937 (Proceedings of the Society of Antiquaries of Scotland, 1938)
The remains of Bronze Age occupation were stratified below Viking/medieval layers at Jarlshof and included stone dwelling, walls, hearths, middens and paved floors. Stone and quartz tools were found in large numbers. Other artefacts included bone tools, querns and a carved bone plaque.